WISDOM Project - XIII. Different molecular structure populations and collision-driven turbulence in the dwarf lenticular galaxy NGC404 - Liu, L; Bureau, M; Li, G-X; Davis, GA; Nguyen, DD; Liang, F; Choi, W; Smith, M; Iguchi, S (Oxford University Press, 2022)
We present a study of molecular structures (clumps and clouds) in the dwarf galaxy NGC 404 using high-resolution (≈ 0.86 × 0.51 pc2 ) Atacama Large Millimeter/sub-millimeter Array 12CO(2-1) observations. We find two distinct regions in NGC 404: a gravitationally-stable central region (Toomre parameter 𝑄 = 3 − 30) and a gravitationally-unstable molecular ring (𝑄 ≲ 1). The molecular structures in the central region have a steeper size – linewidth relation and larger virial parameters than those in the molecular ring, suggesting gas is more turbulent in the former. In the molecular ring, clumps exhibit a shallower mass – size relation and larger virial parameters than clouds, implying density structures and dynamics are regulated by different physical mechanisms at different spatial scales. We construct an analytical model of clump-clump collisions to explain the results in the molecular ring. We propose that clumpclump collisions are driven by gravitational instabilities coupled with galactic shear, that lead to a population of clumps whose accumulation lengths (i.e. average separations) are approximately equal to their tidal radii. Our model-predicted clump masses and sizes (and mass – size relation) and turbulence energy injection rates (and size – linewidth relation) match the observations in the molecular ring very well, suggesting clump-clump collisions is the main mechanism regulating clump properties and gas turbulence in that region. As expected, our collision model does not apply to the central region, where turbulence is likely driven by clump migration.